ROBUST CONTROL DESIGN FOR A CLASS OF UNCERTAIN FIFTH-ORDER LASER SYSTEMS - Yeong-Jeu Sun; Sheng-Chieh Chen; Ting-Chia Chang; Wei-Chun Liao; Sheng-Wei Huang; Yu-Chi Ho (Galaxy International Interdisciplinary Research Journal, 2024)
This paper aims at a class of uncertain 5D laser dynamic systems, seeking a linear controller that is cheap and easy to produce in hardware, so that the entire system can achieve stability. Using differential and integral inequalities combined with control theory, a linear controller guaranteed to achieve global exponential stability will be derived. Besides, the guaranteed exponential convergence rate will be estimated. Finally, multiple numerical simulation results are provided to illustrate the correctness of the main theorem of this article and the design process of the linear controller.